2016
DOI: 10.1136/gutjnl-2015-311238
|View full text |Cite
|
Sign up to set email alerts
|

Integrated genomic analysis of recurrence-associated small non-coding RNAs in oesophageal cancer

Abstract: Objective Oesophageal squamous cell carcinoma (ESCC) is a heterogeneous disease with variable outcomes that are challenging to predict. A better understanding of the biology of ESCC recurrence is needed to improve patient care. Our goal was to identify small non-coding RNAs (sncRNAs) that could predict the likelihood of recurrence after surgical resection and to uncover potential molecular mechanisms that dictate clinical heterogeneity. Design We developed a robust prediction model for recurrence based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…MiRNAs are another important class of regulatory noncoding RNAs involved in liver diseases. (36) The most up-regulated miRNA in this study was miR-1269a (73-fold), which has been linked with relapse and metastasis of colorectal cancer, (37) relapse of squamous cell esophageal carcinoma, (38) and proliferation of HCC by down-regulation of forkhead box O1 (FOXO1). (39) One interesting down-regulated miRNA in our study was miR-4485-3p, which was found deregulated in a gastric cancer cell line (40) and shown to block angiogenesis in Kaposi's sarcoma.…”
Section: Discussionmentioning
confidence: 85%
“…MiRNAs are another important class of regulatory noncoding RNAs involved in liver diseases. (36) The most up-regulated miRNA in this study was miR-1269a (73-fold), which has been linked with relapse and metastasis of colorectal cancer, (37) relapse of squamous cell esophageal carcinoma, (38) and proliferation of HCC by down-regulation of forkhead box O1 (FOXO1). (39) One interesting down-regulated miRNA in our study was miR-4485-3p, which was found deregulated in a gastric cancer cell line (40) and shown to block angiogenesis in Kaposi's sarcoma.…”
Section: Discussionmentioning
confidence: 85%
“…Finally, the 381 genes differentially expressed in TET subgroups between CIN and others (P<10 −7 , FDR <10 −7 , and fold change >2) were defined as CIN gene set (Supplementary Table S1). To determine mRNA signatures identifying the molecular subtypes of validation cohort 2 and melanoma cohort (19), we adopted a previously developed model (20). Briefly, gene-expression data in the training set were combined to form a series of classifiers according to the compound covariate predictor (CCP) algorithm and the robustness of the classifier was estimated by the misclassification rate determined during leave-one-out cross-validation (LOOCV) of the training set.…”
Section: Methodsmentioning
confidence: 99%
“…miRNAs are another important class of regulatory non-coding RNAs involved in liver diseases [24,25,58]. The most dramatically deregulated miRNA in our samples was miR-1269a (73-fold upregulated), which has been reported associated with colorectal carcinoma relapse and metastasis [59], relapse of esophageal squamous cell carcinoma [60], and proliferation of HCC via downregulation of FOXO1 [61]. However, we only detected an slight downregulation of FOXO1 (2.9-fold), which suggests that other targets of miR-1269a may also be involved in the HCC pathology.…”
Section: Discussionmentioning
confidence: 73%